Neoliberal restructuring in Turkey: From state to oligarchic capitalism - Roy Karadag (Max Planck Institute for the Study of Societies, 2010)
How have neoliberal reform policies changed Turkey's political economy? The aim of this paper is to counter claims of convergence towards a liberal capitalist order. Given the historical dynamics of the political embeddedness of Turkey's economy, after 1980, transformations in the state and the economy institutionalized the erosion of Turkish state capitalism. Due to the consolidation of new elite cartels, political fragmentation, and continuing systemic corruption involving networks comprising political and economic elites, what emerged as a result of restructuring is an oligarchic form of capitalism. It is currently undergoing further institutional changes, the outcome of which will depend closely on the power resources and strategies of the incumbent moderate Islamist Justice and Development Party. – – Welche Folgen hatten die neoliberalen Reformen nach 1980 für die politische Ökonomie der Türkei? Der Autor argumentiert gegen weitverbreitete Annahmen einer weltweiten Konvergenz hin zu liberalen kapitalistischen Ordnungen. Zwar wurde das Ende des türkischen Modells des Staatskapitalismus von den neoliberalen Strukturanpassungsprogrammen herbeigeführt, jedoch verhinderten die spezifischen Dynamiken der politischen Einbettung der türkischen Wirtschaft einen Übergang zum liberalen Kapitalismus. Vielmehr hat sich eine oligarchische Variante herausgebildet, deren besondere Merkmale politische Fragmentierung, geringere infrastrukturelle Staatsmacht und systemische Korruptionsverflechtungen zwischen politischen und ökonomischen Eliten sind. Die Wirtschaftsreformen der regierenden moderat islamischen Partei für Gerechtigkeit und Entwicklung sind somit auch kritisch zu bewerten, denn sie wirken nicht losgelöst von Machtansprüchen und -interessen.
Keywords: 300